THE PROBLEMS OF TRANSLATION OF OIL AND GAS TERMS-METAPHORS FROM ENGLISH INTO UZBEK LANGUAGE («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This paper identifies cultural challenges in the translation of terms-metaphors in the oil and gas sphere in English and Uzbek languages. Metaphorization of words that are commonly used in our speech is known as one of the sources of new terminological units, which creates a deep understanding of the semantic functions of the terms used in the oil and gas sector. The absence of a detailed semantic analysis of oil and gas metaphors in English and Uzbek languages, as well as a structured framework for translating them, can create difficulties in cross-cultural communication.
Keywords: Oil and gas industry, terminology, metaphorization, translation, cultural aspects, association, nomination.